DIAGNOSTIC VALUE OF FINE-NEEDLE ASPIRATION BIOPSY IN PATIENTS WITH THYROID CANCER AND HASHIMOTO THYROIDITIS - Stojkovska, Natasha; Kostovska, Irena; Stojanoski, Sinisha (Department of Anaesthesia and Reanimation Faculty of Medicine, “Ss. Cyril and Methodius” University, Skopje, R.N.Macedonia, 2025)
Introduction: Thyroid nodules are a common finding in clinical practice, with prevalence ranging from 2-6% on physical examination, 19–35% on ultrasound, and 8–65% in autopsy studies. Their incidence increases with age and is more frequent in women, individuals with iodine deficiency, and those previously exposed to ionizing radiation. Hashimoto’s thyroiditis may alter cytological interpretation and affect diagnostic accuracy.
Keywords: Hashimoto’s thyroiditis; thyroid carcinoma; fine-needle aspiration biopsy (FNAB)